Developing an index for the orthodontic treatment need in paediatric patients with obstructive sleep apnoea: a protocol for a novel communication tool between physicians and orthodontists. Issue 9 (18th September 2014) - Altalibi, Mostafa; Saltaji, Humam; Roduta Roberts, Mary; Major, Michael P; MacLean, Joanna; Major, Paul W
Abstract : Introduction: Sleep disordered breathing in the paediatric population can manifest as an array of different systemic symptoms; among them is a distinct malocclusion and craniofacial phenotype. Emerging research suggests that the treatment of this malocclusion and/or craniofacial phenotype through orthodontic intervention may help with the symptoms of these patients. Selecting the patients who would benefit from orthodontic treatment can be a difficult task for the physician with minimal dental training. Therefore the aim of this study is to develop a simple index to be used by medical professionals to identify those paediatric patients with orthodontic treatment needs who may benefit their obstructive sleep apnoea (OSA) symptoms. Methods and analysis: The methodology in this project has been devised through the WHO's recommendations on developing an index, with modifications based on the specific needs of this study. Based on the available literature, a draft index will be produced and subjected to multiple iterative revisions based on the feedback from: the Index Development Group, a group of multidisciplinary and internationally acclaimed experts in the field; the External Review Group, a group of potential end users and interested parties and the Steering Committee. Once the index has been formalised, it will be subjected to a pair of reliability tests using physicians and orthodontists scored 2 weeks apart. Subsequently, the index will be validated using dichotomous responses from orthodontists on whether they would treat a patient for OSA symptoms, and comparing the responses to the score of the index on the same patient. Ethics and dissemination: The index will be translated into French and will be presented in orthodontic and medical conferences, workshops, seminars, round table discussions, and free copies for download will be made available on the website of the University of Alberta Interdisciplinary Airway Research Clinic (iarc.ualberta.ca). Furthermore, the index will be published in a peer-reviewed medical journal to further increase the exposure of the index.